Membrane Ultrafiltration Of Treated Palm Oil Mill Effluent (POME) - Nik Sulaiman, Nik Meriam; Ling, Kin Ling (2004)
The oil palm industry and its processing have always been linked with the environment. The wastes generated have significant impact on the environment if not properly managed. Palm oil mill effluent (POME), which is the liquid discharge, comprises mainly organic compounds originating from biodegradable materials and is readily decomposed by anaerobic and aerobic microorganisms. The current treatment technology of POME is largely biological in nature. These processes require large acreage of land and do not always achieve the discharge limits. This paper described a study on the potential use of membrane technology to treat POME from the final discharge pond. The first part of the study investigated the establishment of characteristics of the various ponds within the current POME wastewater treatment plant. The membrane study essentially used hollow fiber membrane of MWCO ranging from 30K to 100K. The results showed that the hollow fiber membrane with MWCO 100K gave higher fluxes compared to the MWCO 30K, however the former membrane gave better quality permeate. The quality of permeate achieved from the membrane with MWCO 30K gave reductions in COD, SS, TKN and ammoniacal-N of 97.66%, 98%, 53.85% and 61.91% respectively. However color removal may require further treatment.